2020
DOI: 10.3389/fphys.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

Air Exposure Affects Physiological Responses, Innate Immunity, Apoptosis and DNA Methylation of Kuruma Shrimp, Marsupenaeus japonicus

Abstract: Air exposure stress is a common phenomenon for commercial crustacean species in aquaculture and during waterless transportation. However, the antioxidant responses to air exposure discussed in previous studies may be insufficient to present the complexities involved in this process. The comprehensive immune responses, especially considering the immune genes, cell apoptosis, and epigenetic changes, are still unknown. Accordingly, we investigated the multifaceted responses of Marsupenaeus japonicus to air exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 92 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…Tissue apoptosis is normally induced by exposure to environmental stresses in aquatic animals such as fish (AnvariFar et al, 2017). Similar phenomena have also been reported in crustaceans; for example, ammonia exposure, air exposure, and cold shock may induce apoptosis in the hepatopancreas of L. vannamei (Chang et al, 2009;Liang et al, 2016;Wang et al, 2020). In this study, we demonstrated that exposure to water with high or low acidity and high or low salinity significantly increased the number of apoptotic cells in the gills of L. vannamei.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Tissue apoptosis is normally induced by exposure to environmental stresses in aquatic animals such as fish (AnvariFar et al, 2017). Similar phenomena have also been reported in crustaceans; for example, ammonia exposure, air exposure, and cold shock may induce apoptosis in the hepatopancreas of L. vannamei (Chang et al, 2009;Liang et al, 2016;Wang et al, 2020). In this study, we demonstrated that exposure to water with high or low acidity and high or low salinity significantly increased the number of apoptotic cells in the gills of L. vannamei.…”
Section: Discussionsupporting
confidence: 84%
“…TUNEL assays and DAPI staining were conducted to detect gill tissue damage under multiple stresses according to a previous description ( Wang et al, 2020 ). The number of apoptotic cells in the gills was determined using the in situ Cell Death Detection Kit (Roche, United States) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…194,195 In addition, DNA methylation and many histone modifications have been identified in a number of crustaceans, including shrimp and crabs. [196][197][198] In summary, more efforts are needed to promote the application of pan-genomics, 3D genomics, and epigenomics to crustacean research. The application of genomic resources in the genetic breeding of farmed crustaceans is mainly concentrated on shrimp and crabs.…”
Section: Utilization Of Multiple Novel Genomic Approaches In Crustace...mentioning
confidence: 99%
“…Epigenomic analyses have been performed in some crustaceans, e.g., the marbled crayfish and Daphnia pulex 194,195 . In addition, DNA methylation and many histone modifications have been identified in a number of crustaceans, including shrimp and crabs 196–198 . In summary, more efforts are needed to promote the application of pan‐genomics, 3D genomics, and epigenomics to crustacean research.…”
Section: Perspectives Of Crustacean Genomics For Aquaculturementioning
confidence: 99%
“…Furthermore, alterations in water quality parameters, such as ammonia/nitrate levels, and exposure to environmental pollutants can instigate oxidative stress and potentially inflict damage to DNA in crustaceans, thereby potentially modulating epigenetic changes [ 188 , 189 , 190 ]. Additionally, air availability has been shown to influence DNA methylation patterns in kuruma shrimps, coinciding with changes in apoptosis and physiological responses [ 191 ]. Moreover, feeding regimes, entailing carefully devised plans encompassing diet composition, nutrient intake, and schedule, can exert significant impacts on the epigenetic changes associated with shrimp immunity and defense functions.…”
Section: Applications Of Epigenetics For Immunity Enhancement and Dis...mentioning
confidence: 99%